Il collo di bottiglia della rappresentanza di genere. Le elette nel Parlamento Italiano nel nuovo millennio (2001-2018) - Sampugnaro, Rossana (SocietàMutamentoPolitica, 2021)
The essay analyzes the policies of rebalancing gender representation in Italy, examining the main approaches and their constituent elements. More specifically, the aim is to document the transformation of the opportunities structure for access to legislative Assemblies for women in the Italian context. Following a diachronic approach, the consistency of the female representation in the Chamber of Deputies from 2001 to 2018 is analyzed. The analysis considers the distribution of female members of Parliament with respect to regional election constituencies and political parties and, at the same time, the evolution of regulatory measures in favor of the rebalancing of representation. The study shows that the presence of women in national political institutions only depends to a limited degree on the introduction of the quota system, introduced by the Rosatellum Law (2018). Italy, as in the past, shows itself to be a multi-speed country that, while pursuing gender equality in places of representation through incremental regulatory adjustments, has already achieved a de facto rebalancing in some areas of the country.